New Insights into Active Faulting in Sulawesi, Indonesia - Patria, Adi; Titu-Eki, Adept; Daryono, Mudrik Rahmawan (Directorate for Research and Community Services, Institut Teknologi Bandung, 2026)
This study investigates the active tectonics of Sulawesi, Indonesia, a seismically active region at the convergence of the Pacific, Australian, and Eurasian plates. We analyze the geological influence on faulting styles and kinematics across the island by integrating geological, geodetic, and geophysical data. Our analysis, which includes geomorphic interpretations, reevaluation of GPS velocities, and earthquake catalogs, reveals diverse deformation regimes in Sulawesi. The North Arm exhibits thrust faulting associated with the subduction zone and normal faulting due to extensional deformation on the overriding plate. The East Arm is dominated by strike-slip faulting along the Balantak fault. Central Sulawesi exhibits prominent seismic activity along the Palu-Koro and Matano faults. West Sulawesi is characterized by a combination of thrust and strike-slip faulting. Lithotectonic units on each arm of Sulawesi are closely related to crustal thickness. The volcanic and plutonic province on the North and West Arms has a thicker crust, while the metamorphic and ophiolite belts in central Sulawesi, and the East and Southeast Arms have thinner crust. Some major faults form boundaries between lithotectonic units, and the transitions between the major strike-slip faults coincide with lithotectonic changes, suggesting a geological influence on the distribution of faults. The North Arm exhibits extension related to subduction rollback, evidenced by normal faulting and divergence motion. Central Sulawesi shows a transition from contraction in the north of the Matano fault, accommodated by thrust faults, to extension east of the Palu-Koro fault. The Southeast Arm is also dominated by strike-slip along the Kolaka fault.